Emergence of Hyalomma marginatum and Hyalomma rufipes adults revealed by citizen science tick monitoring in Hungary. Issue 5 (25th April 2022) - Földvári, Gábor; Szabó, Éva; Tóth, Gábor Endre; Lanszki, Zsófia; Zana, Brigitta; Varga, Zsaklin; Kemenesi, Gábor
Abstract: Hyalomma ticks are important vectors of Crimean‐Congo haemorrhagic fever virus (CCHFV) and other pathogens. They are frequently carried as immatures from Africa, the Middle East and Mediterranean areas to temperate Europe via migratory birds and emergence of adults has been reported in many countries where it has so far been considered non‐endemic. This study aimed to implement the first steps of the DAMA (Document, Assess, Monitor, Act) protocol by monitoring the potential arrival of adult Hyalomma ticks in Hungary applying citizen‐science methods. Ticks were collected from April to December 2021 by asking volunteer participants through a self‐made website to look for large, quickly moving, striped‐legged hard ticks on themselves, their pets and livestock. Owing to an intensive media campaign, the project website had more than 31, 000 visitors within 7 months; 137 specimens and several hundred photos of hard ticks were submitted by citizen scientists from all over the country. Beside Ixodes ricinus, Dermacentor reticulatus, Dermacentor marginatus and Haemaphysalis inermis, a specimen from a dog was morphologically identified as a male Hyalomma marginatum and another removed from a cow as a male Hyalomma rufipes . The dog and the cow had never been abroad, lived approximately 280 km apart, so the two Hyalomma observations can be considered separate introductions. Amplification of the partial mitochondrial cytochrome C oxidase subunit I gene was successfully run for both specimens. Sequencing confirmed the morphological identification for both ticks. Based on the phylogenetic analyses, the Hy. marginatum individual most likely belongs to the Eurasian population and the Hy. rufipes tick to a clade of mixed sequences from Europe and Africa. We summarize the scattered historical reports about the occurrence of Hyalomma ticks and CCHFV in Hungary. Our data highlight the effectiveness of citizens science programmes in the monitoring and risk assessment of CCHFV emergence and preparedness in the study area.